1998
DOI: 10.1159/000012262
|View full text |Cite
|
Sign up to set email alerts
|

Do Patients with Panic Disorder Show a Memory Bias?

Abstract: Background: Cognitive models of panic disorder are becoming more and more influential. Therefore, research specifying cognitive processes related to panic disorder is needed. The present study investigated memory bias for panic-related material in patients with panic disorder. Methods: Memory bias for panic-related material was investigated experimentally by a memory task requiring classification of panic-related and non-panic-related words. Sixty patients with panic disorder and 60 controls with no diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Anxious patients receiving an active drug were found to be more likely to report positive events and less likely to report negative events than patients receiving placebo [32]. Patients with panic disorder showed a memory bias for panic-related material during active illness [33]. In life events research, a delay in the interview until the acute disturbance has passed [34]results in a less distorted history.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…Anxious patients receiving an active drug were found to be more likely to report positive events and less likely to report negative events than patients receiving placebo [32]. Patients with panic disorder showed a memory bias for panic-related material during active illness [33]. In life events research, a delay in the interview until the acute disturbance has passed [34]results in a less distorted history.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…These questions make even more sense when an increased attentional bias is present, i.e., if the task involves emotional processing, such as in exposure to faces or words that are reminiscent of the disorder. 5,12,[17][18][19][20][21] Another question concerns the possible relationship between a decrease in processing speed and a change in executive functions. This question stems from one study, which hypothesized that differences in this area in one group of patients could be a result of the group itself being more prone to difficulty in behavioral strategies.…”
Section: Discussionmentioning
confidence: 99%
“…10 Another article showed a difference in the time taken to recognize panic-related words in patients with PD with or without agoraphobia (n=60) when compared to a control group (n=60). 19 The other two articles used neutral words and words related to the disorder; in both studies, PD patients showed an attentional bias for information related to the disorder. 20,21 One of the studies compared patients with PD (n=15) to a control group (n=15), 20 and the other study compared patients with OCD (n=18), patients with PD (n=15), patients with hypochondriasis (n=14) and a control group (n=19).…”
Section: Affective Processing Of Faces and Wordsmentioning
confidence: 99%